Criminological Review of the Crime of Theft with Violence in Bandar Lampung - Hasan, Zainudin; Fitaloka, Dinda Aura; Ramadhani, Fadilla Rizka; Ismayleyda, Zahra; Pasha, Riska Kurnia (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Theft with violence is a criminal act that often occurs in society. This action not only harms the victim materially, but also emotionally and psychologically. The implications of violent theft in the justice system are very important to consider, because this relates to justice and the protection of society. A review of violent theft shows that these acts are often committed by perpetrators from low socio-economic backgrounds and are often involved in other criminal activities. Implications for the justice system include a fair and effective law enforcement process, as well as the need for rehabilitation for perpetrators so they can return to society as productive individuals. The research method used is normative juridical by approaching rules, regulations, norms and all policies in force in Indonesia relating to the scope of violent theft. The results of this research show that the crime of theft with violence is in positive law. The crime of theft with violence is regulated in Article 365 of the KUHP which states that it is punishable by imprisonment for 9 (nine) years. Theft is preceded, accompanied or followed by violence or threats of violence. is threatened with imprisonment for a maximum of twelve years if it is committed at night in a closed yard, if it is committed by two or more people, if it is committed by two or more people, if it enters the house by breaking or using a fake key and if the act results in serious injury. A maximum prison sentence of up to 15 (fifteen) years is threatened if the act results in death.